6 - Des lançados aux expatriés : « l’Ethnie Blanche » entre les fleuves Sénégal et Casamance: https://doi.org/10.4314/ad.v34i2.57375 - Crosas Armonia Pérez (Africa Development, 2009)
The region located between the Senegal and the Casamance rivers has a long history of the presence of Western white men. Although the characters and situations modeled by the ‘White Ethnic Group’ over time have been very varied, there are characteristics that are repeated, continuities associated with the ambiguity of social status, gender relations or economic specializations, on the boundary between both local and global levels. The paper explores the durability of a cultural boundary, suggesting avenues of research from the figure of lançados. The analysis shows indications, repeated parallels between the effects of variations in boundary conditions on the collective ‘White’, swaying be- tween maintaining their identity and integrating into indigenous communi- ties. The author believes that a long-term perspective would help under- stand the current articulation of contingents of cooperation volunteers who come to the region, an nderstanding that could be extrapolated to other areas on the continent.